2007
DOI: 10.1177/030089160709300308
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Serum Levels and Prognostic Value in Malignant Gliomas

Abstract: Although a prospective study with large sample size is warranted, serum EGFR extracellular domain may be potentially useful as a biological marker of gliomas for prediction of prognosis and follow-up after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 27 publications
2
27
1
1
Order By: Relevance
“…In contrast to a previous study [18], we were unable to detect any difference in serum EGFR levels between patients with GBM, anaplastic glioma, and healthy controls. We used the same ELISA assay as Quaranta et al, but included also anaplastic oligodendrogliomas, oligoastrocytomas, and GBMs with oligodendroglioma component.…”
Section: Serum Egfr Is Not Related To Egfr Status In the Tumor Tissuecontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to a previous study [18], we were unable to detect any difference in serum EGFR levels between patients with GBM, anaplastic glioma, and healthy controls. We used the same ELISA assay as Quaranta et al, but included also anaplastic oligodendrogliomas, oligoastrocytomas, and GBMs with oligodendroglioma component.…”
Section: Serum Egfr Is Not Related To Egfr Status In the Tumor Tissuecontrasting
confidence: 99%
“…Measuring serum levels of EGFR extracellular domain (ECD) has provided additional information on tumor aggressiveness and outcome in various types of malignancies [14][15][16][17]. Quaranta et al found elevated serum EGFR levels also in patients with glioblastomas compared to anaplastic astrocytomas or controls [18]. However, the association of serum EGFR levels to EGFR overexpression and amplification status in tumor tissue or to other molecular markers has not previously been studied.…”
Section: Introductionmentioning
confidence: 99%
“…For example, serum-borne epidermal growth factor receptor (EGFR) levels were shown to be significantly different when comparing healthy controls with malignant glioma patients and EGFR serum levels are associated with prognosis (2). Levels of a proliferation-inducing ligand (APRIL) have been found to be elevated in the sera of glioblastoma (GBM) patients when compared to non-tumor controls (3).…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al data show that tumour a v b 3 integrin stands as a therapeutic target for the prevention of skeletal metastases. The nonpeptide antagonist of a v b 3 (PSK1404) showed a meaningful antitumour effects in experimental breast and ovarian cancer bone metastasis [58]. Vitaxin, an antihuman a v b 3 antibody is currently in clinical trials as a treatment for metastatic melanoma and results indicate that this drug may be instrumental in inhibiting the advancement of lifethreatening cancers [59].…”
Section: Therapeutic Targetsmentioning
confidence: 99%